Aircraft-lightning electrodynamics using The transmission line model part I: review Of the transmission line model - Thirukumaran, S.; Hoole, P.R.P; Harikrishnan, R.; Jeevan, K.; Pirapaharan, K.; Ratnajeevan, S.; Hoole, H. (Progress In Electromagnetics Research M, Vol. 31, 85–101, 2013, 2013)
This work presents a self-consistent and self-contained model to study and analyze aircraft-lightning electrodynamics. In this paper, we review the well developed and reported transmission line model of the cloud-to-ground (CG) lightning return stroke. Subsequently, the incorporation of a circuit model of the aircraft into the return stroke model is considered. The direct hit characteristics of aircraft body lightning currents for both CG and GC (ground- to-cloud) are important when designing protection, shielding and filtering systems for airborne electronic and electrical systems within the aircraft system. Moreover, the model will allow design of aircraft structure and geometry to minimize energy dissipation into the aircraft structure and systems. Basic electromagnetic theory is used to show the validity of considering the return stroke as a transverse magnetic wave along a transmission line. A distributed transmission line model for the aircraft and the return stroke channel of the lightning is used to simulate the return strokes of CG and GC flashes. The effects of the aircraft geometry with sharp edges are included in the computation of aircraft capacitance values, both distributed as well as lumped values. The paper compares electric currents, channel voltages, the rate of change of current and the frequency spectrum along the lightning channel of the return strokes for CG and GC flashes with aircraft attached to the channel.